Liver resection for multimodal treatment of breast cancer metastases: identification of prognostic factors - Hoffmann, Katrin; Franz, Clemens; Hinz, Ulf; Schirmacher, Peter; Herfarth, Christian; Eichbaum, Michael H. R.; Büchler, Markus W.; Schemmer, Peter (Annals of surgical oncology, 2010)
Liver resection (LR) within a multimodal treatment concept of hepatic metastases (HM) that results from breast cancer has been controversially discussed. The aim of this study was to evaluate the outcome of LR in patients with hepatic breast cancer metastases.
Gesehen am 13.03.2023